2022
DOI: 10.1186/s13018-022-03285-0
|View full text |Cite
|
Sign up to set email alerts
|

Medial pivot prosthesis has a better functional score and lower complication rate than posterior-stabilized prosthesis: a systematic review and meta-analysis

Abstract: Purpose We aimed to compare the postoperative clinical efficacy and safety of medial pivot (MP) prosthesis and posterior-stabilized (PS) prosthesis in the treatment of knee osteoarthritis (KOA). Methods All studies involving MP and PS prosthesis in PubMed, EMBASE, Cochrane Library, and Web of Science were searched since the establishment of the database. The included outcomes were knee range of motion (ROM), functional score, radiographic results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Jones et al reported better sagittal stability using an MC insert [11]. Petersen et al [18], Shi et al [21] and Cacciola et al [4] also report better stability and excellent clinical and patient reported outcomes in patients undergoing TKA using a medial pivot insert. Sabatini et al [20] similarly reported good to excellent results using a third‐generation prosthesis system with a MC polyethylene insert.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jones et al reported better sagittal stability using an MC insert [11]. Petersen et al [18], Shi et al [21] and Cacciola et al [4] also report better stability and excellent clinical and patient reported outcomes in patients undergoing TKA using a medial pivot insert. Sabatini et al [20] similarly reported good to excellent results using a third‐generation prosthesis system with a MC polyethylene insert.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on the rationale behind the evolution of the MC polyethylene insert design in providing a greater level of stability with minimum constraint [9, 18, 21]. Alesi et al [1].…”
Section: Discussionmentioning
confidence: 99%
“…The ball-and-socket medial compartment provides knee stability, and the relatively flat surface on the lateral compartment allows for greater anterior-posterior translation. Multiple studies have reported superior clinical patient outcomes in MP-TKA compared to PS-TKA [ 1 , 15 , 16 , 17 , 18 ]. In contrast, some other studies have shown no difference between the two groups [ 2 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%